The loyal republic : traitors, slaves, and the remaking of citizenship in Civil War America - Mathisen, Erik (Civil War America (Series), 2018)
Mathisen tells the story of how Americans attempted to define what it meant to be a citizen of the United States, at a moment of fracture in the republic's history. As the author demonstrates, prior to the Civil War, American national citizenship amounted to little more than a vague bundle of rights. But during the conflict, citizenship was transformed.